UJI PRAKLINIK ANTIHIPERURISEMIA SECARA IN VIVO PADA MENCIT PUTIH JANTAN GALUR BALB-C DARI EKSTRAK DAUN SALAM (Syzigium polyanthum Walp) DAN DAUN BELIMBING WULUH (Averrhoa bilimbi L.) - Muhtadi, .; Suhendi, Andi; Wahyuningtyas, Nurcahyanti; Sutrisna, EM. (Universitas Muhamadiyah Surakarta, 2014)
Antihyperuricemia activity in vivo testing has been done of single and combined extracts of Salam (Syzigium polyanthum Walp) and Belimbing Wuluh leaves (Averrhoa bilimbi L.), and also standardized extracts. Salam leaves extraction and Belimbing Wuluh leaves carried by the water solvent. Dried extract of each ingredient had been done antihyperuricemia preclinical in vivo testing against male white mice strain Balb-C induced by potassium oxonate dose of 250 mg / kg b.w. Antihyperuricemia preclinical in vivo testing results showed that the single extracts of Salam and Belimbing Wuluh at a dose of 200 mg / kg b.w. had lower activity levels of uric acid in the blood serum of male white mice, respectively 0.640 and 0.680. While the activity of the combination of extracts of Salam-Belimbing Wuluh is 1.380.Keywords: Antihyperurisemia preclinical in vivo testing; Salam leaves extract, Belimbing Wuluh leaves extract, male white mice Balb-C